2017
DOI: 10.1111/ijfs.13715
|View full text |Cite
|
Sign up to set email alerts
|

Formation and stability of emulsions stabilised by Yucca saponin extract

Abstract: Summary Yucca saponin extract containing steroidal saponins was examined for its interfacial and emulsifying properties. For this purpose, we produced oil‐in‐water emulsions and tested their stability against environmental stresses (pH, ionic strength, heating and freeze‐thawing). Yucca saponin extract was highly surface‐active and formed negatively charged submicron‐sized emulsions at low surfactant‐to‐oil ratio. The emulsions were stable at pH 5–9 and showed only minor increase in droplet size when heated up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 28 publications
3
31
0
3
Order By: Relevance
“…Furthermore, we determined a critical micelle concentration (CMC AW ) of ~0.5% (w/w) as well as a surface load (Γ AW ) of 3.8 mg m −2 . Significantly lower CMC and Γ values have been previously reported for Quillaja (CMC = ~0.01%; Γ AW = 2.9 mg m −2 ) and yucca saponin extracts (CMC = ~0.1%; Γ AW = 1.7 mg m −2 ), indicating that these extracts are more efficient at surface tension reduction, mostly likely because of their much higher content of saponins (~9% for both extracts) (Yang et al ., ; Ralla, Salminen, Tuosto, & Weiss, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we determined a critical micelle concentration (CMC AW ) of ~0.5% (w/w) as well as a surface load (Γ AW ) of 3.8 mg m −2 . Significantly lower CMC and Γ values have been previously reported for Quillaja (CMC = ~0.01%; Γ AW = 2.9 mg m −2 ) and yucca saponin extracts (CMC = ~0.1%; Γ AW = 1.7 mg m −2 ), indicating that these extracts are more efficient at surface tension reduction, mostly likely because of their much higher content of saponins (~9% for both extracts) (Yang et al ., ; Ralla, Salminen, Tuosto, & Weiss, ).…”
Section: Resultsmentioning
confidence: 99%
“…Saponin stabilized emulsions were recently studied by several groups. In [115], a very good thermal stability of medium chain triglyceride (MCT) Miglyol-in-water emulsions, stabilized by Yucca saponin extract, was reported in the pH range between 5 and 9. In a separate study, the emulsions stabilized by Quillaja saponins were found to be sensitive to the variations in the pH and electrolyte concentration [116,117].…”
Section: (D) Saponin Stabilized Emulsionsmentioning
confidence: 99%
“…Saponin molecules comprise a hydrophilic region, containing rhamnose, galactose, xylose, fucose, or glucuronic acid, and a hydrophobic counterpart including gypsogenic or quillaic acid, whose combination ensures the amphipathic character of the molecule, enabling its surfactant behavior [20]. Moreover, the abundance of saponins in nature facilitates their commercial production [21,22] from a wide range of natural matrices, with Quillaja bark being one of the most used [23,24].…”
Section: Introductionmentioning
confidence: 99%